2013
DOI: 10.1105/tpc.113.112714
|View full text |Cite
|
Sign up to set email alerts
|

Gene Networks and Chromatin and Transcriptional Regulation of the Phaseolin Promoter in Arabidopsis

Abstract: The complete lack of seed storage protein expression in vegetative tissues and robust expression during embryogenesis makes seed development an ideal system to study tissue-specific expression of genes. The promoter for the Phaseolin (phas) gene, which encodes the major seed storage protein in bean (Phaseolus vulgaris), is activated in two sequential steps: Phaseolus vulgaris ABI3-like factor (Pv-ALF)-dependent potentiation and abscisic acid-mediated activation. In this study, a heterologous in vivo Pv-ALF/pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Our data now place BBM/AIL proteins directly upstream of the LAFL/AGL15 genes. There is some evidence that LAFL proteins might act upstream of AILs: a Phaseolus vulgaris ABI3-like factor (PvALF) binds and activates Arabidopsis CHO1/EMK/AIL5/ PLT5 (Sundaram et al, 2013), and Arabidopsis FUS was shown to bind BBM, PLT2, AIL6/PLT3, and PLT7, although transcriptional regulation was not investigated (Wang and Perry, 2013). In contrast, the lack of AIL deregulation after inducible overexpression of LEC1, ABI3, FUS3, or LEC2 (Braybrook and Harada, 2008;Yamamoto et al, 2010;Junker et al, 2012;Mönke et al, 2012) suggests that there is no direct feedback of LAFLs on AILs.…”
Section: Discussion Bbm-mediated Embryogenesis Requires Lafl Genesmentioning
confidence: 99%
“…Our data now place BBM/AIL proteins directly upstream of the LAFL/AGL15 genes. There is some evidence that LAFL proteins might act upstream of AILs: a Phaseolus vulgaris ABI3-like factor (PvALF) binds and activates Arabidopsis CHO1/EMK/AIL5/ PLT5 (Sundaram et al, 2013), and Arabidopsis FUS was shown to bind BBM, PLT2, AIL6/PLT3, and PLT7, although transcriptional regulation was not investigated (Wang and Perry, 2013). In contrast, the lack of AIL deregulation after inducible overexpression of LEC1, ABI3, FUS3, or LEC2 (Braybrook and Harada, 2008;Yamamoto et al, 2010;Junker et al, 2012;Mönke et al, 2012) suggests that there is no direct feedback of LAFLs on AILs.…”
Section: Discussion Bbm-mediated Embryogenesis Requires Lafl Genesmentioning
confidence: 99%
“…Although our knowledge about the PLT-mediated induction of SE is rather fragmentary, a recent finding that PLT3, EMK/PLT5 and PLT7 stimulate auxin biosynthesis through the activation of YUC genes (YUC1 and YUC4) to control phyllotaxis (Pinon et al 2013) implies a possible role of PLTs in the auxin-related mechanism of SE induction. An EMK/PLT5-controlled induction of SE may also be related to GA and an encoded TF was reported to negatively impact GA biosynthesis in the control of the storage protein accumulation in Arabidopsis seeds (Sundaram et al 2013).…”
Section: Plethora Genes-the Integrators Of Hormonal Inputsmentioning
confidence: 99%
“…S1). This promoter is the most abundant seed storage protein in the common bean (Phaseolus vulgaris) and is stringently turned off during all vegetative stages of plant development (Sundaram et al, 2013). It was also demonstrated that this promoter is induced constitutively during the maturation and desiccation stages of seed development (Fait et al, 2011).…”
Section: Creating Transgenic Arabidopsis Seeds Expressing Atd-cgsmentioning
confidence: 99%
“…This fragment was cut from the pCE vector using SphI and introduced with that enzyme into the pCEPH vector, which contains the phaseolin promoter (Shaul and Galili, 1992). This promoter is the most abundant seed storage protein in the common bean (Phaseolus vulgaris) and is stringently turned off during all vegetative stages of plant development (Sundaram et al, 2013). It was demonstrated that this promoter is induced constitutively during the maturation and desiccation stages of seed development (Fait et al, 2011).…”
Section: Generation Of Transgenic Arabidopsis Seeds Expressing Atd-cgmentioning
confidence: 99%